Suspended sediment transport in coastal zone by tidal flow. Part II: Comparison with the experiment - S. M., Antsyferov; T. M., Akivis (Vietnam Journal of Mechanics, 2004)
The aim of the study is to develop methods for prediction of the vertical distribution of characteristics of sand and aleurite sediment suspended by tidal flow for the averaging time either divisible by tidal period (the first order model) or much less than it is (the second order one). The bottom is assumed to be erodible with possible formation of ripples. Part II: The solution developed was verified by the extensive data set of measurements in Bahia Blanca Bay in Western Atlantic using sediment traps. The methods of trap data interpretation and the procedure for comparison measured data with model results have been developed. The comparison results seem to be quite satisfactory for both types of models.